SOCS3 Promotes ALV-J Virus Replication via Inhibiting JAK2/STAT3 Phosphorylation During Infection - Mo, Guodong; Fu, Huali; Hu, Bowen; Zhang, Qihong; Xian, Mingjian; Zhang, Zihao; Lin, Ling; Shi, Meiqing; Nie, Qinghua; Zhang, Xiquan (Frontiers in Cellular and Infection Microbiology, 2021)
Avian leukosis virus subgroup J (ALV-J) is an oncogenic retrovirus that causes immunosuppression and neoplastic diseases in poultry. Cytokine signal transduction inhibitor molecule 3 (SOCS3) is an important negative regulator of the JAK2/STAT3 signaling pathway and plays certain roles in ALV-J infection. It is of significance to confirm the roles of SOCS3 in ALV-J infection and study how this gene affects ALV-J infection. In this study, we assessed the expression of SOCS3 gene in vivo and in vitro, and investigated the roles of SOCS3 in ALV-J infection using overexpressed or interfered assays with the SOCS3 in DF-1 cells. The results showed that the SOCS3 expression of ALV-J infected chickens was different from uninfected chickens in the spleen, thymus and cecal tonsil. Further, SOCS3 is mainly expressed in the nucleus as determined by immunofluorescence assay. Overexpression of SOCS3 in DF-1 cells promoted the replication of ALV-J virus, and the expression of interferons (IFNα and INFβ), inflammatory factors (IL-6 and TNFα) along with interferon-stimulating genes (CH25H, MX1, OASL, and ZAP). Conversely, interference of SOCS3 showed the opposite results. We also observed that SOCS3 promoted ALV-J virus replication by inhibiting JAK2/STAT3 phosphorylation. In conclusion, SOCS3 promotes ALV-J replication via inhibiting the phosphorylation of the JAK2/STAT3 signaling pathway. These results would advance further understanding of the persistent infection and the viral immune evasion of ALV-J virus.